The Identification and Significance of a Thr→Pro Polymorphism in Kringle IV Type 8 of Apolipoprotein(a) - Prins, J; Lues, F R; van der Hoek, Y Y; Kastelein, J J.P; Bouma, B N; van Rijn, H J.M (Thrombosis and Haemostasis, 1997)
Elevated plasma levels of lipoprotein(a) [Lp(a)] represent a significant independent risk factor for the development of atherosclerosis. Interindividual levels of apo(a) vary over 1000-fold and are mainly due to inheritance that is linked to the locus of the apolipoprotein(a) [apo(a)] gene. The apo(a) gene encodes multiple repeats of a sequence exhibiting up to 85% DNA sequence homology with plasminogen kringle IV (K.IV), a lysine binding domain. In our search for sequence polymorphisms in the K.IV coding domain, we identified a polymorphism predicting a Thr→Pro substitution located at amino acid position 12 of kringle IV type 8 of apo(a). The functional and clinical significance of this polymorphism was analysed in a case-control study and by comparing the in vitro lysine binding characteristics of the two Lp(a) subtypes.The case-control study (involving 153 subjects having symptomatic atherosclerosis and 153 age and gender matched normolipidemic controls) revealed an overall allele frequency for the Thr12-→Pro substitution in kringle IV type 8 of 14% and a negative association between presence of the Pro12-subtype and symptomatic atherosclerosis (p <0.03). The in vitro lysine binding studies, using Lp(a) isolated from subjects homozygous for either Thr12 or Pro12 in K.IV type 8, revealed comparable lysine-Sepharose binding fractions for the two subtypes. The binding affinity (Kd) for immobilised plasmin degraded des- AA-fibrin (DesafibTM-X) was also comparable for the two subtypes, however a decreased maximal attainable binding (Bmax) for immobilised desafibTM-X was observed for the Pro12-subtype Lp(a).